KONTEKTUALISASI FAKTOR-FAKTOR PENDIDIKAN DALAM KITAB TA’LIMU AL-MUTA’ALLIM DENGAN PENDIDIKAN MASA KINI - Moh. Ali Mas'ud (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2019)
Abstract Throughout human history education is a very important requirement that is necessary so that education is researched and developed how to discover new concepts as a logical consequence of the times. These developments then lead to modernization whose consequence is to start questioning the relevance of old or classic concepts. the question raised by those who disagree is that old methods cannot answer the development of science and technology. Is it true? what about the classic book that is often used as a reference in the educational process, namely Ta'lim Muta'llim ?. The Book of Ta'lim Muta'alim is a yellow book in the area of ??origin, which is around the Middle East, this yellow book is called Al-Pole Al-Qadimah as a rival of Al-Pole Al-Ashriyah. The research method is qualitative with a literature approach. While data sources are primary and secondary data sources. The primary virgin is the book Ta'limu al-Muta'allim, while the secondary source is various sources of reading related to the discussion. In Education which is based on the yellow book, it has succeeded in forming a moral society and adapting to different levels of intelligence, from Talib (student) and mutha'alim to pious or mu'alim (kyai). The yellow books will all refer to the translation of the Qur'an and Al-Hadith or take the legitimacy from these two sources of teachings.